RESEARCH OF A CHEMICAL COMPOSITION OF GROUND DEPOSITS OF UPPER COURSES OF THE KUBAN RIVER - Inna Vladimirivna Begday; Konstantin Yurevich Shkarlet; Konstantin Victorovich Harin; I. Yu. Katorgin (Наука. Инновации. Технологии, 2022)
Results of research of a chemical composition of ground deposits of the Kuban River and its inflows are given in the top part of the pool in the territory of the Karachay-Cherkess Republic. The pollution reasons are analyzed.